PENGELOLAAN WAKAF DI PONDOK PESANTREN AL-WASILAH LEMO POLEWALI MANDAR PERSPEKTIF HUKUM ISLAM - Riswandi; Alimuddin; Musyfikah Ilyas (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2024)
The main problem of this research is the management of waqf at al-wasilah Islamic boarding school Lemo Polewali Mandar from the perspective of Islamic law. The subject matter is then formulated into three problem formulations namely, 1. How is the development of waqf at the Al-Wasilah Lemo Polewali Mandar Islamic Boarding School, 2. How is the review of Islamic law on the development of waqf at the Al-Wasilah Lemo Polewali Mandar Islamic Boarding School, and 3. What are the inhibiting factors for waqf development in Al-Wasilah Lemo Polewali Mandar Islamic Boarding School. This type of research is field research, which is descriptive qualitative in nature. The research approach used is the Sociological Approach, Syar'i Approach, Juridical Approach. The source of research data is the management of the al-wasilah Islamic boarding school, Lemo. Data collection methods used are interviews and observation. Then data management and analysis techniques, namely data that is not related to numbers and not related to statistical analysis. The results of this study indicate that the waqf development method at al Wasilah Lemo Islamic Boarding School uses four main elements, namely, planning, organizing, leadership, and monitoring processes. Its management and development are in accordance with Islamic law, where the foundation program's waqf provisions have fulfilled its pillars and conditions. The obstacles faced by the development of waqf at the al wasilah Lemo Islamic boarding school include the lack of public understanding of waqf, a lack of funds to manage land and other waqf assets, a lack of human resources and the absence of a waqf agency at the al wasilah Lemo Islamic boarding school.